Ekonometrický model poptávky po elektrické energii - komparativní studie vztahu maloobchodních a velkoobchodních cen v EU - Franěk, Martin (Vysoké učení technické v Brně. Fakulta podnikatelská, 2022)
Předmětem této diplomové práce je vytvoření ekonometrických modelů vysvětlující tvorbu cen elektřiny se zaměřením na srovnání prostředí maloobchodních a velkoobchodních cen za období let 2010 až 2020. Model bude vytvořen pro prostředí České republiky a vybrané členské země EU. Dílčími cíli práce je rešerše odborné literatury, vytvoření databáze pro výpočtovou část, vytvoření modelu v příslušném statistickém softwaru (GRETL a IBM SPSS Statistics 25), testování stability modelu a diskuse a hodnocení výsledků.

The subject of this master´s thesis is to create an econometric models explaining the formation of electricity prices with a focus on comparing the environment of retail and wholesale prices between years 2010 and 2020. The model will be created for the environment of the Czech Republic and another chosed EU member country. The partial goals of the work are the research of professional literature, the creation of a database for the computational part, the creation of the model in the appropriate statistical software (GRETL and IBM SPSS Statistics 25), testing the stability of the model and the discussion and evaluation of results.
An Econometric Model of Electricity Demand in the Czech Republic - a Comparative Study of the Relationship between Retail and Commercial Prices in EU
Keywords: elektřina; cena elektrické energie; ekonometrický model; statistika; ekonometrická analýza; regresní model; prognóza; časové řady; autokorelace; heteroskedasticita; regresní analýza; korelační analýza; Česká republika; Rakousko; electricity; electricity price; econometric models; statistics; econometric analysis; regression models; forecast; time series; autocorrelation; heteroskedasticity; regression analysis; correlation analysis; Czech Republic; Austria